Renegotiation Versus Brexit: The Question of the UK's Constitutional Relationship with the EU1. (21st February 2019) - Vasilopoulou, Sofia; Keith, Dan
Abstract: This article examines how the British public perceived UK Prime Minister David Cameron's plan to renegotiate his country's relationship with the EU. It asks whether attitudes towards renegotiation followed a similar pattern to attitudes towards Brexit. It asks: are preferences towards renegotiation and Brexit related, and did British citizens perceive them as conflicting or complementary? We modelled the similarities and differences between these two types of preferences, which allowed us to classify the attitudes into four patterns: unconditional europhiles, rejectionist eurosceptics, risk‐averse eurosceptics and power‐seeking eurosceptics. Using a large‐N cross‐sectional survey conducted in the UK in April 2015 ( n = 3000), our findings suggest that similar utilitarian concerns underpinned both types of preferences; but education and partisan cues differentiated them. Our findings have implications for understanding the result of the UK referendum. They also highlight the complex considerations that drive citizens' attitudes towards the EU and help us predict the scope of public acceptance of EU reform initiatives by other governments.